Formation of Karakalpak Literature of the 21st Century - Maratovna, Otarbaeva Fatima (European Journal of Life Safety and Stability (2660-9630), 2023)
in this article we consider Karakalpakstan itself, the literature of Karakalpakstan. At the same time, we analyze the history of the appearance of the Karakalpak literature. And of course we will analyze why the Karakalpak literature itself is needed.